Can AI Medical Devices Receive De Novo Classification? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2019)
> Can AI Medical Devices Receive De Novo Classification?
Keywords: FDA Regulation and Compliance; Medical; Devices; Receive; Artificial Intelligence; Machine Learning; Healthcare